Successful management of wilt diseases in mango, guava and banana: An integrated approach - Singh, Deepak; Shukla, P K; Damodaran, T (Indian Horticulture, 2026)
Wilt diseases in perennial fruit crops such as mango, guava, and banana pose a major threat to sustainable production owing to the soil-borne nature of the pathogens and limited management options. Mango wilt (Ceratocystis fimbriata), guava wilt complex (Fusarium oxysporum f. sp. psidii), and banana wilt (Fusarium oxysporum f. sp. cubense) collectively cause severe yield losses, orchard decline, and long-term soil infestation, rendering conventional control measures largely ineffective. To address this challenge, ICAR–CISH, Lucknow, has developed and validated integrated wilt management strategies and modules encompassing soil health restoration, deployment of resistant/tolerant rootstocks, fungicide application, use of bioformulations (ICAR-FUSICONT), and farmers’ participatory management practices. Field validation of the mango wilt management module across multiple hotspot areas has achieved effective disease suppression, leading to improved plant vigour, enhanced productivity, and prolonged orchard longevity. The success of this integrated, eco-smart approach provides a sustainable, scalable, and resilient solution for managing soil-borne wilt pathogens in major subtropical fruit crops.